Problems of governance in South Asia - Panandiker, V. A. Pai; Centre for Policy Research (New Delhi, India) (Delhi : Konark, 2000)
Contributed articles.
"Under the auspices of Centre for Policy Research, New Delhi."
Includes bibliographical references and Index.
Keywords: Democracy -- South Asia; South Asia -- Politics and government